Stolen focus : why you can't pay attention--and how to think deeply again - Hari, Johann (Crown, 2022)
"Our ability to pay attention is collapsing. From the New York Times bestselling author of Chasing the Scream and Lost Connections comes a groundbreaking examination of why this is happening-and how to get our attention back. Like so many of us, Johann Hari was finding it much harder to focus than he used to. He found that a life of constantly switching from device to device, from tab to tab, is diminishing and depressing. He tried all sorts of self-help solutions-even abandoning his phone for three months-but in the long-term, nothing seemed to work. So Hari went on an epic journey across the world to interview the leading experts on human attention and to study their scientific findings-and learned that everything we think we know about this crisis is wrong. In the U.S., teenagers now focus on a task for only sixty-five seconds on average, and office workers manage only three minutes. We think this inability to focus is a personal flaw, an individual failure to exert enough willpower over our devices. The truth is even more disturbing: Our focus has been stolen by powerful external forces, and the science shows that these forces have been ramping up for decades-leaving us uniquely vulnerable, when social media arrived, to corporations determined to raid our attention for profit. These forces have been so successful that our collapse in attention is behind many of the wider problems society faces. In Stolen Focus, Hari embarks on a thrilling journey, taking readers from veterinarians who diagnose dogs with ADHD, to Silicon Valley dissidents who exposed social media companies' furtive attempts to hack our focus; from a favela in Rio where everyone lost their attention in a particularly catastrophic way, to an office in New Zealand that discovered a remarkable technique to restore their workers' attention. In this urgent, deeply researched book, Hari shows that if we understand the twelve true causes of this crisis-from the collapse of sustained reading to the disruption of boredom to rising pollution-we, as individuals and as a society, can finally begin to solve it by staging an "attention rebellion." Finally, we have a way to get our focus back"--